Renewable energy policy in times of crisis: A comparison between Spain and Portugal - Jörgens, H.; Guerreiro, L. (12th Biennial Conference of the ECPR Standing Group on the European Union, 2024)
In response to the financial crisis, Portugal and Spain changed their support schemes for the deployment of renewable energy in 2013, when both countries were led by a centre-right majority government. At the time, both countries had adopted ambitious subsidy-based policies and, consequently, were leaders in the transition to renewable energies, with high levels of installed capacity in solar and wind. However, during the crisis, the two countries followed divergent policy paths: Portugal revised its renewable energy policy, but maintained its overall goals and policies, while Spain revoked all subsidy contracts. To explain this divergence, we analyse parliamentary debates and media coverage in the period from 2011 to 2013. We use the Discourse Network Analyser (DNA) software to identify actor coalitions and their respective policy preferences. We argue that energy transition policy choices are intertwined with the interests of the most important energy companies but are tenuously linked to the underlying market economy and to energy transition discourses.